FORMULASI ORALLY DISINTEGRATING TABLET (ODT) ASETOSAL DENGAN VARIASI KONSENTRASI KOMBINASI AVICE - Hayatus Sa'adah; Yulistia Budianti S.; Akhmad Andy Sandra (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2019)
Acetylsalicylic acid or better known as acetosal or aspirin is a drug that has efficacy as an antiplatelet which is widely used as a drug to prevent and treat stroke. Currently acetosal is often found in many preparations, one of which is in conventional tablet preparations. Stroke sufferers really need a drug in tablet dosage form that is easy to consume, has a relatively fast duration of drug action, and with more practical drug administration. Therefore, an acetosal preparation is made in the form of Orally Disintegrating Tablet (ODT) which has several advantages, including being more practical to use because it can be consumed without using water and can be used by patients who are difficult to swallow conventional tablets. Research conducted on acetosal ODT formulation with variations in the combination concentration of Avicel PH 102 and mannitol as filler material. In this study, the physical properties of ODT acetosal were tested by varying the combination concentration of Avicel PH 102 and mannitol as a filler with a ratio of F1 = 0: 1, F2 = 0.25: 0.75, F3 = 0.5: 0.5 , F4 = 0.75: 0.25, and F5 = 1: 0. The ODT evaluation was carried out in the form of examining the weight uniformity test, hardness test, friability test, and tablet disintegrating time test. The results of the study obtained the best formula is F4 with a comparison of Avicel PH 102 and manitol 0.75: 0.25 that meets the requirements of physical properties of ODT with the average value of tablet weight uniformity test 382.5 mg ± 0.007, tablet 2 hardness test, 52 kg / cm2 ± 0.396, tablet friability test 0.53% ± 0.153, and tablet disintegrating time test 21 seconds ± 3.605.